The role of regulations in the fertilizer sector of Pakistan - Ali, Mubarik; Ahmed, Faryal; Channa, Hira; Davies, Stephen (International Association of Agricultural Economists, 2015)
The regulatory and institutional setup in fertilizer processing, distribution, marketing, and utilization has resulted in a scenario where the input has failed to reach its full potential in terms of use on crops and has threatened the long term sustainability of the sector. Urea production has historically been subsidized massively by the government, a subsidy which is becoming increasingly difficult to maintain in terms of the fiscal cost and the availability of domestic natural gas. The subsidy on urea production has promoted its imbalanced use and undermined other important soil inputs like phosphorus, potash, and micronutrients. Meanwhile the yield response of urea has tapered off and its’ per hectare use is fast reaching its optimal level. The regulatory framework needs to be re-worked to promote modernization of existing capacity and the use of environmentally friendly fertilizer products. Increasing dependence on imports needs to be considered rather than exhausting the existing gas resources. Fertilizer policy should encompass the broader needs of all stakeholders, rather than just focus on the natural gas requirements of urea producers. Ali, Mubarik; Ahmed, Faryal; Channa, Hira; Davies, Stephen